Silver(I) and Copper(II) Complexes of 1,10-Phenanthroline-5,6-Dione Against Phialophora verrucosa: A Focus on the Interaction With Human Macrophages and Galleria mellonella Larvae - Granato, Marcela Q.; Mello, Thaís P.; Nascimento, Renata S.; Pereira, Marcos D.; Rosa, Thabatta L. S. A.; Pessolani, Maria C. V.; McCann, Malachy; Devereux, Michael; Branquinha, Marta H.; Santos, André L. S.; Kneipp, Lucimar F. (Frontiers in Microbiology, 2021)
Phialophora verrucosa is a dematiaceous fungus that causes mainly chromoblastomycosis, but also disseminated infections such as phaeohyphomycosis and mycetoma. These diseases are extremely hard to treat and often refractory to current antifungal therapies. In this work, we have evaluated the effect of 1,10-phenanthroline-5,6-dione (phendione) and its metal-based complexes, [Ag(phendione)2]ClO4 and [Cu(phendione)3](ClO4)2.4H2O, against P. verrucosa, focusing on (i) conidial viability when combined with amphotericin B (AmB); (ii) biofilm formation and disarticulation events; (iii) in vitro interaction with human macrophages and (iv) in vivo infection of Galleria mellonella larvae. The combination of AmB with each of the test compounds promoted the additive inhibition of P. verrrucosa growth, as judged by the checkerboard assay. During the biofilm formation process over polystyrene surface, sub-MIC concentrations of phendione and its silver(I) and copper(II) complexes were able to reduce biomass and extracellular matrix production. Moreover, a mature biofilm treated with high concentrations of the test compounds diminished biofilm viability in a concentration-dependent manner. Pre-treatment of conidial cells with the test compounds did not alter the percentage of infected THP-1 macrophages; however, [Ag(phendione)2]ClO4 caused a significant reduction in the number of intracellular fungal cells compared to the untreated system. In addition, the killing process was significantly enhanced by post-treatment of infected macrophages with the test compounds. P. verrucosa induced a typically cell density-dependent effect on G. mellonella larvae death after 7 days of infection. Interestingly, exposure to the silver(I) complex protected the larvae from P. verrucosa infection. Collectively, the results corroborate the promising therapeutic potential of phendione-based drugs against fungal infections, including those caused by P. verrucosa.